2002
DOI: 10.1175/1520-0442(2002)015<1573:mionhc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Indices of Northern Hemisphere Cyclone Activity, Winters 1949–99

Abstract: The National Centers for Environmental Prediction-National Center for Atmospheric Research (NCEP-NCAR) reanalysis is used to estimate time trends of, and analyze the relationships among, six indices of cyclone activity or forcing for the winters of 1949-99, over the region 20Њ-70ЊN. The indices are Eady growth rate and temperature variance, both at 500 hPa; surface meridional temperature gradient; the 95th percentile of near-surface wind speed; and counts of cyclones and intense cyclones. With multiple indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 57 publications
10
92
1
Order By: Relevance
“…Various metrics can be used to diagnose mid-latitude cyclone activity, including eddy kinetic energy (Hu et al, 2004), temporal variability of sea-level pressure, temperature or meridional wind (Harnik and Chang, 2003), the meridional temperature gradient, and the Eady growth rate (Paciorek et al, 2002). Some studies have used the probability distribution of sea-level pressure as a diagnostic of cyclone frequency (Murazaki and Hess, 2006;Lin et al, 2008;Racherla and Adams, 2008).…”
Section: Detection and Tracking Of Mid-latitude Cyclonesmentioning
confidence: 99%
“…Various metrics can be used to diagnose mid-latitude cyclone activity, including eddy kinetic energy (Hu et al, 2004), temporal variability of sea-level pressure, temperature or meridional wind (Harnik and Chang, 2003), the meridional temperature gradient, and the Eady growth rate (Paciorek et al, 2002). Some studies have used the probability distribution of sea-level pressure as a diagnostic of cyclone frequency (Murazaki and Hess, 2006;Lin et al, 2008;Racherla and Adams, 2008).…”
Section: Detection and Tracking Of Mid-latitude Cyclonesmentioning
confidence: 99%
“…This aspect has been explored in many recent publications based on observational datasets: While some authors (e.g., Schinke, 1993;Lambert, 1996;Paciorek et al, 2002) identified significant changes in extra-tropical cyclone activity…”
Section: Introductionmentioning
confidence: 99%
“…Serreze et al, 1993;Sinclair, 1994;Serreze et al, 1997;Lambert et al, 2002;Paciorek et al, 2002;Cao and Zhang, 2004;Zhang et al, 2004). Some tracking schemes have been applied to both cyclones and anticyclones (Pezza and Ambrizzi, 2003).…”
Section: Introductionmentioning
confidence: 99%